L’essor de l’activité minière à l’Ouest du Kenya - Joseph Bohbot (EchoGéo)
In Kakamega County, in Western Kenya, mining activity and in particular artisanal gold mining offers today more attractive income than its traditional agricultural sector. However, artisanal miners remain limited in the exploitation of gold resources due to their lack of capital and technical knowledge. Other actors, with greater resources, are able to position themselves in gold mining while cohabiting with these artisanal gold miners. Consequently, mining activity now contributes to a significant economic dynamism, accelerating the development of this western area of Kenya.